The Impact Of Financial Distress On Company Value - Sudyantara, Smita Catur; Yuwono, Amrih; Kurniawan, Rahmad; Sumantyo, Fransiscus Dwikotjo Sri; Sari, Mila Diana (Sharia Journal and Education Center Publishing, 2026)
This study aims to investigate the effect of financial distress on firm value in the manufacturing sector listed on the Indonesia Stock Exchange. Firm value is a crucial investor perception, but it is often distorted when a firm shows signs of financial distress. Using a quantitative approach, this study measures financial distress through a modified Altman Z-Score model and firm value through Tobin's Q. Panel data is analyzed using the E-Views 12 statistical tool through a panel data regression test to determine the best model between Common Effect, Fixed Effect, or Random Effect. The results show that financial distress has a negative and significant impact on firm value. This finding confirms signaling theory, where conditions of financial distress send a bad signal to the market, which ultimately reduces investor confidence and stock prices. This study contributes to management in conducting early detection of potential bankruptcy to maintain the stability of firm value in the capital market.